Gender-specific trajectories of academic achievement in Chinese elementary school students: Relations with life satisfaction trajectories and suicidal ideation trajectories. (June 2023) - Tian, Lili; Li, Xiaoyu; Chen, Xueyi; Huebner, E. Scott
Abstract: This study explored heterogeneous developmental trajectories of academic achievement and their relations to trajectories of life satisfaction and trajectories of suicidal ideation among Chinese elementary school students. A sample of 547 students (55.0% boys; M age  = 9.00 years, SD  = 0.76 at Time 1) completed a packet of measures on five occasions across two years, using 6-month intervals. Three distinct trajectories of academic achievement were identified: "high-stable" (86.28%), "low-increasing" (8.94%), and "low-decreasing" (4.78%). Girls demonstrated higher academic achievement than boys. Students displaying adverse developmental trends in academic achievement were more likely to show adverse trends in life satisfaction. Finally, trajectories of academic achievement and trajectories of suicidal ideation were related for girls, but not boys. Programs promoting academic achievement may require adaptations for the differing genders and start as early as elementary school. Highlights: The findings revealed three distinct trajectories of academic achievement. Girls demonstrated better academic achievement than boys. Students in the positive developmental group showed the best mental health. More attention should be given to gender difference in academic achievement.